Kepadatan Larva Nyamuk Aedes aegypti di Lingkungan Desa Karangsari, Kecamatan Sempu, Kabupaten Banyuwangi dan Pemanfaatannya sebagai Leaflet - Jihan Afkarina Hanum (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Dengue fever (DF) is one of the vector-borne diseases that remains a public health problem in Indonesia, especially in residential areas. The transmission of DF is greatly influenced by the presence and density of Aedes aegypti mosquito larvae as the main vector. This study aims to determine the density of Aedes aegypti mosquito larvae in the environment of Karangsari Village, Sempu District, Banyuwangi Regency, and to utilize the results of this study as educational media in the form of leaflets. This study is a descriptive study using the larval survey method. Data collection was carried out through house inspections and water container inspections to identify the presence of Aedes aegypti mosquito larvae. The data obtained were analyzed using larval index indicators, namely the House Index (HI), Container Index (CI), and Breteau Index (BI), to determine the density of larvae and the potential risk of dengue transmission. Furthermore, the research results were used in the preparation of leaflets as educational media, which were then tested for feasibility through validation by subject matter experts, media experts, and the general public. The results of the study indicate that the HI, CI, and BI values in the study area are in the moderate density category, which indicates that there is still a potential risk of dengue transmission. The results of the leaflet validation test show that the average value is in the highly feasible category, so the leaflet is considered suitable for use as a public health education medium. Thus, this study is expected to provide information on the density of Aedes aegypti larvae and support dengue fever prevention efforts through the use of appropriate educational media.
FINALISASI oleh Agus 2026 Ju ni 10
Keywords: Aedes aegypti; larvae density; larvae index; leaflet